Utilization of dry distillers grains and charcoal as nitrogen fertilizer in corn - Shroyer, Kyle J. (Kansas State University, 2010)
With the increase in bio-energy production there is also an increase in by-products. Without proper disposal, these by-products might cause future economic and/or ecological problems. Land application has potential as a disposal and/or nutrient cycling method if these by-products have nutritive value for agricultural crops. The purpose of the study was to compare the use of two by-products of bio-energy production, dry distillers grains (ethanol) and charcoal(pyrolysis), as fertilizer with urea in corn (Zea mays L.). The experiment consisted of four location-years in Kansas. Treatments were dry distiller’s grains (DDG) no-till and tilled for four location-years and char no-till and tilled for three location-years. No-till urea was used as a baseline for comparison at all location-years. The Nitrogen rates ranged from 45 to 180 kg N ha-1. All source material was spring applied before tillage and planting. The corn yields for DDGs and urea were the almost the same across tillage treatments and locations. For DDG no-till, DDG tilled, and urea, the rates at which to achieve the same yields were 97, 111, 78 kg N ha-1, respectively. Corn yields for char at all rates and tillage treatments were the same as no fertilizer. The char, because of immobilization or lack of decomposition, did not contribute to the nitrogen needs of the corn. Neither material showed any inhibitory or otherwise negative effects on the corn in terms of grain yield compared with the control. But both DDGs and char had to have large amounts of material applied to achieve the same amount of nitrogen as urea. Land application of DDGs and char has potential merit for disposal/nitrogen cycling with DDGs being preferred for its nitrogen contribution.
Keywords: charcoal; biochar; DDG; dry distillers grains; no-till; corn; Agriculture, Agronomy (0285)